Table of Content - -, (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content1. The impact of strategic leadership on improving the organizational health of Yemeni private universitiesCo-Prof. Zayed Naji Shawesh, Mr. Abdullah Ahmed Al-Shakhfir2. The role of transformational leadership in promoting social responsibility (Applied study on Directorate of Health Affairs in Aseer)Mr. Abdullah Mubarak Said Alkhudran3. The validity of electronic evidence in Omani lawMr. Hamad Salem Hamad Al-Alawi4. The Effect of Job Burnout Stability (Applied Study on the Health Sector in Asir Region in KSA- 1444AH)Mrs. Asma Mohamed Al-Shehri, Mrs. Reem Awad Abo Dahesh, Mrs. Sara Hussein Al Sultan, Mrs. Bayan Abdullah Asiri , Mrs. Jamilah Salman Al-Maliki5. Functions of the criminal investigation authority in the Saudi partial Criminal procedure SystemDr. Yasmeen Ahmad Mohammed6. The Impact of the Work Environment and Services on the Degree of Job Satisfaction of Faculty Members A field Study at Nile Valley University – Sudan (2021 – 2022 AD)Dr. Omer Mustafa Ali Osman7. Purchase Intentions and Luxury Brands: A Study on Consumer Behaviour in Saudi ArabiaMrs. Nora Toffaha, Prof. Maha Abdullah Al-Dabbagh
Keywords: Journal of Economic, Administrative and Legal Sciences